PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP PERILAKU PESERTA DIDIK DI SMAN 1 KELUMBAYAN - Joko Prihatin (Jurnal Pendidikan Islam, 2025)
Islamic learning which only takes the form of advice, commands, prohibitions and memorization cannot shape students' morals, but requires examples and direct practice so that good character can be integrated with students. Islamic holidays and Islamic holidays are good opportunities to educate religious feelings in the hearts of students. Learning can be defined as an activity designed to help someone learn a new ability and/or value. Therefore, the Islamic learning plan must include all three. Likewise, teachers who teach according to plan must even be able to expand on the material presented because this is useful for cultivating a sense of religion and awakening enthusiasm in the hearts of students. Meanwhile, the problem formulation in this research is: 1) How does Islamic Religious Education Learning affect the behavior of students at SMA Negeri 1 Kelumbayan. 2) What is the behavior of students in Islamic religious education subjects at SMAN 1 Kelumbayan? 3) How does Islamic Religious Education Learning influence the behavior of students at SMA Negeri 1 Kelumbayan? This type of research uses a quantitative approach, namely a research procedure that uses data collection techniques through questionnaires and documentation. Meanwhile, to collect data, researchers use questionnaires and documentation, then the data taken will be analyzed and used as conclusions from the research results. The results of this research show that there is an influence of Islamic Religious Education learning on the behavior of students at SMA Negeri 1 Kelumbayan. This can be seen from the results of a simple regression test via SPSS 22 that the calculated F value is 11.656 with a significance level of 0.001<0.05, meaning that the significant value is smaller than 0.05, meaning that variable X has an effect on variable Y. From the results of the hypothesis test the result is 0.462 using the product moment correlation formula. Meanwhile, rtable at the 5% significance level is 0.2480. Thus, rxy of 0.462 is greater than rtable, therefore rxy of the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, so it is known that the Islamic Religious Education learning variable on the character of students at SMA Negeri 1 Kelumbayan shows an influence with a sufficient level of interpretation.